JAK2 inhibitor CEP-33779 prevents mouse oocyte maturation in vitro. Issue 4 (12th July 2017) - Wu, Changli; Li, Rong; Luo, Haibing; Xu, Mingfeng; Zhang, Xiujuan
Abstract : The inhibitor CEP-33779 is a specific selective inhibitor of Janus kinase 2 (JAK2). In most somatic cells, JAK2 plays essential roles in cellular signal transduction and in the regulation of cell cycle. Little is known regarding the effects of JAK2 on mammalian oocyte maturation. In the present study, we investigated the effects of CEP-33779 on mouse oocytes' meiosis and the possible mechanisms of JAK2 during mouse oocyte maturation. We detected the distribution of JAK2 during the mouse oocyte maturation. The results showed that JAK2 was mainly distributed in the cytoplasm during maturation. We cultured mouse oocytes with CEP-33779, examined the maturation rate, spindle morphology, and organization of microfilaments during the mouse oocyte maturation. While the rate of germinal vesicle breakdown (GVBD) did not differ between the treated and control groups, the rate of oocyte maturation decreased significantly when treated with CEP-33779. The rate of maturation was 21.14% in treated group and was 81.44% in control group. The results show that CEP-33779 inhibits the maturation of mouse oocytes. There was no obvious difference in the meiotic spindle morphology between the treated and control groups. The results show that CEP-33779 treatment did not disrupt the reorganization of microtubules. The microfilament observation shows that the microfilament did not form actin cap and the spindle stayed at the center of the oocyte in the treated group. CEP-33779 treatment inhibited the maturation of mouse oocytes which might be because of the disruption of formation of the actin cap. These results suggest that JAK2 regulated the microfilaments aggregation during the mouse oocyte maturation.